Problematika Pemenuhan Kebutuhan Hukum Terhadap Kelompok Rentan Dalam Mengakses Keadilan - M. Rizki Yudha Prawira (Jurnal Hukum Lex Generalis, 2024)
This research discusses the problems of vulnerable groups who often face various problems accessing justice. The stigma attached to them and various discriminatory treatments from the public and law enforcement officers are two forms of the problems they face. These factors contribute to negative perceptions and a growing reluctance among these groups to seek justice for their legal troubles. Based on the 2022 Legal Needs Survey report for Vulnerable Groups regarding the behavior patterns of vulnerable groups in resolving legal problems, it was found that vulnerable groups in resolving legal problems indicate that there is a problem. The form of problem portrayed is victim blaming, a perception that tends to be pessimistic when accessing justice, misunderstanding regarding informal mechanisms, and a perception that their efforts to resolve legal problems will not maket he situation getting better.